2021
DOI: 10.1016/j.prevetmed.2021.105473
|View full text |Cite
|
Sign up to set email alerts
|

Household and animal factors associated with sheeppox and goatpox sero-prevalence and identification of high-risk areas in selected States of northern Nigeria

Abstract: Sheeppox and goatpox (SGP) are transboundary, highly contagious diseases affecting sheep and goats with characteristic clinical signs. SGP affect populations of small ruminants in Africa, Asia and the Middle East and, as a result, threaten farmers’ livelihoods. Despite their importance, studies looking at factors that increase the risk of sheeppox-virus (SPPV) and goatpox-virus (GTPV) exposure and infection are limited. A cross-sectional study was conducted in three states of Northern Nigeria (Bauchi, Kaduna a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We observed poor biosecurity measures at outbreak farms including poor carcass disposal, mixing of sick and apparently healthy animals, uncontrolled movement of animals and people on farms, limited disease knowledge, lack of disinfection and no record of screening animals for SGP before purchase. Consistent with previous reports, these practices were positively correlated with SGP seropositivity on investigated cases [ 27 ]. The farmers managed clinical cases with a broad range of antibiotics such as [Oxytetracycline Penicillin and multivitamins] consistent with previous report [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed poor biosecurity measures at outbreak farms including poor carcass disposal, mixing of sick and apparently healthy animals, uncontrolled movement of animals and people on farms, limited disease knowledge, lack of disinfection and no record of screening animals for SGP before purchase. Consistent with previous reports, these practices were positively correlated with SGP seropositivity on investigated cases [ 27 ]. The farmers managed clinical cases with a broad range of antibiotics such as [Oxytetracycline Penicillin and multivitamins] consistent with previous report [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…We were unable to determine the actual time when SGP clinical signs were first observed in investigated flocks because none of the flocks was managed by a professional veterinarian and relied on farmers recall capacity in absence of records. It is therefore likely that we took samples outside the SGP optimal sampling time a period when, detectable neutralizing antibodies are low, explaining low levels [27%] of seroconversion rates in the investigated outbreak small ruminant herds [ 27 ]. Additionally, panic sales that are triggered by suspected SGP outbreaks could have contributed to low seropositivity in investigated outbreak flocks as it was unlikely to find index cases at the farm.…”
Section: Discussionmentioning
confidence: 99%
“…The A34 protein is a glycoprotein present in the outer membrane of the extracellular enveloped virion of poxviruses, involved in cell-to-cell transmission [ 43 ]. Previous studies on the antigenicity of vaccinia’s A34 protein showed its potential as a target candidate to develop an ELISA [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were identified via convenience sampling. Primary data from a survey conducted in 2019 involving 300 randomly selected sedentary herds in Bauchi, Kaduna and Plateau, 100 in each state, was used to obtain herd demographic data and SGP prevalence from the number of households reporting SGP clinical signs ( Adedeji et al, 2021 ). Finally, values missing after literature review, focus group discussion and the survey were obtained from authors who have field and laboratory knowledge and experience in virology, vaccinology, SGP epidemiology, small ruminant husbandry, and animal health programmes within Northern Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…Based on data from the survey in the study area, 97.5 % of young animals were older than 3 months at time of survey. Therefore, 100 % of the reproductive herd and 97.5 % of the young herd are eligible so will be vaccinated ( Adedeji et al, 2021 )…”
Section: Methodsmentioning
confidence: 99%